Pneumatic battery for untethered robotic gripper with the influence of high molecular weight solid electrolyte - Chee, Darren Jian Hui (Nanyang Technological University, 2022)
Commercial robotic grippers are tethered devices, and they are connected to existing pneumatic sources such as compressed-gas tanks, compressors, or pressurized gas supply lines. Additionally, these pneumatic sources are heavy, or they require an external power supply. Thus, they are only suitable for stationary, limited mobility operations. To make robotic grippers untethered, they require an onboard pressure generator where it has to be compact, lightweight, high pressure, quiet and safe. Zinc-air battery has the ability to provide on-board pressure generation while being a power supply on its own while being non-toxic and non-corrosive. Therefore, this report aims to research zinc-air batteries with the influence of a high molecular weight solid electrolyte gripper and to design a pneumatic system for an untethered robotic gripper. This can be achieved by using a PVA molecular weight of 89,000 ∼ 98,000 g/mol for the fabrication of the electrolyte. The solid electrolyte will be a gel polymer electrolyte of PVA and KOH while the experiment will be to fabricate a few electrolytes at various time intervals. It has been observed from this experiment shows with the lesser water content present in the solid electrolyte, the more concentrated it is, which leads to a higher discharging voltage. The voltage of the battery with the least water content is as high as 1.76 V.